Regional and cultivar comparison of Italian single cultivar olive oils according to flavor profiling. Issue 2 (27th December 2012) - Tura, Debora; Failla, Osvaldo; Bassi, Daniele; Attilio, Cristina; Serraiocco, Arnaldo
Abstract Geographical origin, cultivar, and olive ripening stage are important factors which affect the typical flavor profile of extra virgin olive oils. Aromatic compounds and sensorial profiles of "Casaliva", "Frantoio", and "Leccino" olive oils from three different Italian production regions Abruzzo (eastern‐central Italy), Lombardy (northern Italy), and Tuscany (western‐central Italy) were assessed in two cropping years and at three olive ripening stages (green, veraison, and ripe). The chemical aromatic compounds were more effective in discriminating the oils than their sensorial attributes. Oils showed peculiar aromatic and sensorial profiles according to their region of origin. Genetically similar "Casaliva" and "Frantoio" showed also analogous profiles, but distinct from "Leccino". The interaction between regions of cultivation and cultivars significantly affected the flavor profiling. Practical applications: This research provides a sound proof that geographical origin, cultivar, and fruit ripening stage, could play an important interactive role in shaping the flavor profiling of extra virgin olive oils. This represents a scientific basis of the "typicality" concept, which should address the marketing strategies for exploiting of the PDO products.